2021
DOI: 10.1097/01.aoa.0000732572.03502.ef
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Vertical Transmission in Neonates Born to Mothers With Coronavirus Disease 2019 (COVID-19) Pneumonia

Abstract: (Obstet Gynecol. 2020;136:1–3) Studies on the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have mainly focused on nonpregnant patients. There is a need for studies examining vertical transmission and perinatal infection of SARS-CoV-2. This report focuses on neonatal outcomes from 7 pregnant patients with coronavirus disease 2019 (COVID-19), between the dates of January 20, 2020, and February 20, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 0 publications
1
23
0
11
Order By: Relevance
“…This is concordant with the other published case series, although Alzamora et al reported one case of a positive SARS-CoV-2 PCR swab in a neonate born by caesarean section from a severely ill mother [5]. Hu et al also reported one neonate positive for SARS-CoV-2, born by caesarean section from a woman with mild symptoms with a negative amniotic fluid SARS-CoV-2 PCR [6]. Two other case reports raise concerns about vertical transmission based on the presence of IgM and IgG antibodies in two neonates born from mothers with coronavirus disease 2019 (COVID-19) [1,2].…”
Section: To the Editorsupporting
confidence: 88%
“…This is concordant with the other published case series, although Alzamora et al reported one case of a positive SARS-CoV-2 PCR swab in a neonate born by caesarean section from a severely ill mother [5]. Hu et al also reported one neonate positive for SARS-CoV-2, born by caesarean section from a woman with mild symptoms with a negative amniotic fluid SARS-CoV-2 PCR [6]. Two other case reports raise concerns about vertical transmission based on the presence of IgM and IgG antibodies in two neonates born from mothers with coronavirus disease 2019 (COVID-19) [1,2].…”
Section: To the Editorsupporting
confidence: 88%
“…Four studies evaluated the placenta for infectious pathology 27,29,30,54,80,91 . Twenty‐five percentage of these reports documented neonatal SARS‐CoV‐2 infection 75,77,94,100‐105,109 . One case series described positive neonatal RT‐PCR at 36 hours postpartum although amniotic fluid RT‐PCR was negative 100 .…”
Section: What Do We Know About Mother‐to‐child‐transmission Of Sars‐cov‐2?mentioning
confidence: 99%
“…Twenty‐five percentage of these reports documented neonatal SARS‐CoV‐2 infection 75,77,94,100‐105,109 . One case series described positive neonatal RT‐PCR at 36 hours postpartum although amniotic fluid RT‐PCR was negative 100 . Reports from Italy, Peru and Iran attributed neonatal infection to horizontal transmission from RT‐PCR positive mothers via breastfeeding without masks (respiratory droplets) and vaginal delivery (exposure to genital secretions) 101‐103 due to maternal seroconversion a few days postpartum.…”
Section: What Do We Know About Mother‐to‐child‐transmission Of Sars‐cov‐2?mentioning
confidence: 99%
“…A study finds that SARS-CoV-2 RNA can be detected in placental and fetal membrane sample, however, none of infants tested positive for SARS-CoV-2 in the first 5 days of life (107). In another study, seven neonates are tested within the first 24-36 h of life and only one has positive result (108). Although a neonate was diagnosed with COVID-19 36 h after birth, SARS-CoV-2 RNA was not detected in the placenta and cord blood (109).…”
Section: Transmission Modelsmentioning
confidence: 98%